Construire la relation éducative : postulat d'éducabilité, bienveillance et altruisme - Tommy Terraz; Amandine Denimal (Université de Provence, 2018)
This study, which is part of the field of the philosophy of education, aims to question from a reflexive, speculative and logical point of view the benevolence of the educator with regard to the postulate of educability. Both a logical assumption and an ethical principle, this postulate requires that the subject be credited a priori and gratuitously as an educable subject. It could serve as an anchor point for the implementation of an ethics of caring in the field of education and training. Our articulation between educational benevolence and the postulate of educability will bring out the concept of altruism. The proposed demonstration, in the form of a syllogism, will lead us to consider that altruism, in that it is unconditional, intimately linked to relational action and to the integration of the « tiers personnel »/« autrui universel », is a necessary and not sufficient condition to allow the advent of a truly educational relationship favouring the emergence of the educated subject as a person in its plural dimensions.